Does exposure to PPO-inhibiting herbicides alter the male-to-female sex ratio of Palmer amaranth? - Mafia M. Rumpa; Sirwan Babaei; Ronald F. Krausz; David J. Gibson; Eric J. Miller; Karla L. Gage (Weed Technology)
Palmer amaranth, a competitive weed in cotton and soybeans, poses challenges due to its rapid growth, high fertility, and herbicide resistance. Effective management strategies targeting sex ratios could reduce seed production by female plants. Protoporphyrinogen oxidase (PPO-) inhibiting herbicides play a role in the evolving resistance of Amaranthus spp. in the US Midwest. These herbicides may also affect the male-to-female ratio of Palmer amaranth. A 2-yr field experiment (2015 and 2016) was conducted in a soybean field in Collinsville, IL, evaluating various preemergence and postemergence PPO-inhibiting herbicide treatments. Untreated Palmer amaranth populations exhibited a bias toward females. Preemergence application of sulfentrazone and flumioxazin effectively reduced Palmer amaranth density (1.66 plants m–2) throughout the season, whereas postemergence applications of fomesafen and lactofen provided limited control (27 and 31 plants m–2, respectively). Early-season mortality was high (96%) among Palmer amaranth seedlings, especially with pyroxasulfone + fluthiacet-methyl treatment. Fomesafen increased female biomass (28.8%) while reducing male biomass compared to the nontreated control. In 2015, pyroxasulfone + fluthiacet-methyl and acetochlor altered the male-to-female sex ratio compared to the nontreated control, with pyroxasulfone + fluthiacet-methyl reducing the proportion of females (–0.11 M/F) and acetochlor slightly increasing the proportion of males (0.03 M/F), though not different from a 1:1 ratio. In 2016, pendimethalin and flumioxazin (71 g ai ha–1) resulted in a strong female-biased sex ratio, with an almost exclusively female population. In both years, the nontreated control plots (–0.58 and –0.55 M/F) maintained a naturally female-biased sex ratio, deviating significantly from a 1:1 ratio. These findings suggest that specific herbicide treatments can alter the sex ratio. Understanding sex determination in Palmer amaranth holds promise for developing more effective control strategies in the future.